If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -4t Solving 7 = -4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4t' to each side of the equation. 7 + 4t = -4t + 4t Combine like terms: -4t + 4t = 0 7 + 4t = 0 Add '-7' to each side of the equation. 7 + -7 + 4t = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4t = 0 + -7 4t = 0 + -7 Combine like terms: 0 + -7 = -7 4t = -7 Divide each side by '4'. t = -1.75 Simplifying t = -1.75
| 7(5y-4)+2(4y+6)= | | 7(5y-6)+2(4y+6)= | | 2-14=-8t+4t | | 5x^2+11x-66=0 | | 5(y*2-4)=-21y | | 6x^2+x=2 | | 6t*2=7 | | s*2-9=0 | | 4(6x-9)=3(12x-8) | | 6z-5=7z-7 | | 6(y+1)-5=7 | | 7-z=3+z+4-2z | | 2u=u-6 | | 8x-4=(2x+1) | | 2x^2+3y^2-30=0 | | 2w+3=7w+13 | | 4y^2+11y+7=5 | | 5y-8=3y+5 | | 4x-3x-7=6x | | 22-3(c-1)=-3c+25 | | 4k^2+6k-1=0 | | 4x-32=2x | | 2(n-1)=8n-3 | | 6x-1=25 | | 2y-x=8 | | -13(x+1)=-13x-13 | | 9x^2+49x+64=0 | | -5(a+1)=4(a+10) | | 4x-4=4x | | 2x^2+18x+28=0 | | -20x=-4x-6x | | 4*u=28 |